Density and distribution of lymphocytes in pretherapeutic rectal cancer and response to neoadjuvant therapy. (12th June 2020) - Lai, Sicong; Lou, Xiaoying; Fan, Xinjuan; Sun, Weipeng; Deng, Yanhong; Wang, Jianping; Huang, Yan; Dou, Ruoxu
Abstract: Background: Lymphocytic density in rectal cancer has been reported to be associated with therapeutic response, but the role of the lymphocytic distribution pattern remains to be determined. This study aimed to evaluate the association between the distribution and density of lymphocytes in rectal-cancer tissue with tumor response to neoadjuvant therapy. Methods: We retrospectively analysed 134 patients with rectal cancer receiving neoadjuvant therapy within a prospectively maintained cohort. Pretherapeutic biopsy samples were stained with immunohistochemistry (CD4 and CD8). Densities of intratumoral periglandular lymphocytes (IPLs) and tumor-infiltrating lymphocytes (TILs) were assessed separately. Logistic-regression analysis was used to assess associations of lymphocyte densities with tumor regression grade (TRG), controlling for clinicopathological, molecular, and regimen features. Results: Compared with cases in the lowest quartile of CD8 + TILs, those in the highest quartile were significantly associated with better TRG (multivariate odds ratio, 0.23; 95% confidence interval, 0.07 to 0.76; P  <   0.001). In contrast, CD8 + IPLs, CD4 + IPLs, and CD4 + TILs were not significantly associated with TRG ( P  =   0.033, 0.156, and 0.170, respectively). Sensitivity analyses detected no interaction between CD8 + TILs and regimen of neoadjuvant radiation ( P interaction   =   0.831) or chemotherapy ( P interaction   =   0.879) on TRG. Conclusions: Our data suggest that CD8 + TILs, but not IPLs, are independently associated with response to neoadjuvant therapy, regardless of the regimen of radiation or chemotherapy.